2022
DOI: 10.4236/jcc.2022.107007
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Advancement of Cashless Transaction: A Security Analysis of Electronic Payment Systems

Abstract: In recent decades, day-to-day lifestyle requires online payments as easy and simple solutions to several financial transactions, which makes the concept of Electronic payment Systems very popular in the growth of a cashless society. In fact, cashless transactions through simple mobile apps are not merely a concept anymore rather are implemented robustly and being used extensively. On the dark side, obvious financial benefits are making these apps vulnerable to being attacked, which can be successful through se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Furthermore, the review results highlight the weaknesses of present m-banking user authentication schemes as the study found majority of the user authentication techniques used by employed by payment institutions to be vulnerable. This result was reinforced by the findings of Hanif and Lallie (2021), and Moon et al (2022). The authors argued that an ''insecure verification process and poor credentials recovery system'' makes present authentication techniques vulnerable and ineffective.…”
Section: Key Findings Of the Studiesmentioning
confidence: 93%
“…Furthermore, the review results highlight the weaknesses of present m-banking user authentication schemes as the study found majority of the user authentication techniques used by employed by payment institutions to be vulnerable. This result was reinforced by the findings of Hanif and Lallie (2021), and Moon et al (2022). The authors argued that an ''insecure verification process and poor credentials recovery system'' makes present authentication techniques vulnerable and ineffective.…”
Section: Key Findings Of the Studiesmentioning
confidence: 93%
“…Globally, cashless transactions are growing in popularity (Chen & Jiang, 2022;Jakubowska, 2017;Shukur et al, 2022), with steady increases in demand (Alam et al, 2021). These entail the exchange of digital currency or an electrical representation of cash, replacing physical banknotes or coins (Moon et al, 2022). Through Internet banking or mobile banking applications (apps), cashless payments complement the use of physical money (Ong & Chong, 2023).…”
Section: Introductionmentioning
confidence: 99%